F-18-FDG-hybrid-camera-PET in patients with postoperative fever - Meller, J.; Sahlmann, C. O.; Lehmann, K.; Siefker, U.; Meyer, I.; Schreiber, K.; Altenvoerde, G.; Becker, W. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Evaluation of F-18-FDG-hybrid-camera-PET imaging in patients with undetermined postoperative fever (POF). Methods: Prospective study of 18 patients (9 women, 9 men; age 23-85 years) suffering from POF with 2-fluoro-2’-deoxyglucose (F-18-FDG) using a dual headed coincidence camera (DHCC). Surgery had been performed 5-94 days prior to our investigation. 13 of the 18 patients received antibiotic therapy during the time of evaluation. Ten (55%) had an infectious and eight (45%) a non infectious cause of fever. Results: Increased F-18-FDG-uptake outside the surgical wound occurred in 13 regions (infection n = 11, malignancy n = 2). The sensitivity of F-18-FDG-hybrid-camera-PET in imaging infection in areas outside the surgical wound was 86% and the specificity 100%, respectively. Antibiotic therapy did not negatively influence the results of F-18-FDG-scanning. Increased F-18-FDG-uptake within the surgical wound was seen in 8 of 18 patients. The sensitivity of F-18-FDG-hybrid-camera-PET in imaging infection within the surgical wound was 100% and the specificity 56%, respectively. The interval between surgery and F-18-FDG-scanning was significantly shorter in patients with false positive results compared with patients showing true negative results (median 34 vs. 54 days; p = 0,038). Conclusion: In POF-Patients, F-18-FDG transaxial tomography performed with a F-18-FDG-hybrid-camera-PET is sensitive in the diagnosis of inflammation and malignant disease within and outside the surgical wound. Because of the accumulation of the tracer both in granulation tissue and infection, the specificity in detecting the focus of fever within the surgical wound is poor.
Keywords: F-18-FDG-PET; postoperative fever; infection